Perhitungan Cadangan Premi Asuransi Jiwa Berjangka dengan Menggunakan Metode Zillmer dan Fackler - Sitorus, Kristiani; Yulita, Tiara; Lestari, Fuji (Indonesian Journal of Applied Mathematics, 2024)
Human life is never free from risk. Along with the development of the era, humans began to realize the importance of protecting themselves in the event of a risk, including the risk of death. To overcome this, many individuals transfer the risk by registering themselves or their families with life insurance. The life insurance that is focused on is term life insurance, which is a form of protection with a certain period of time that has been set. In order to run its operations properly, insurance companies need to prepare premium reserves with accurate calculations. These calculations can be done through two actuarial methods, namely prospective and retrospective methods. This study uses the Zillmer method (prospective) and the Fackler method (retrospective) for calculating premium reserves. The purpose of this study was to determine the analysis of the results of calculating the premium reserve value from the two methods. The premium reserve values ​​calculated using the Zillmer and Fackler methods were different. At an interest rate of 6.25%, the Fackler method produces a higher premium reserve compared to the Zillmer method. This difference is because the Zillmer method includes other costs such as acquisition costs, administration, and agent commissions in calculating premium reserves. In contrast, the Fackler method does not take these costs into account in its calculations.